META-ANALYSIS: IMPROVING LIFE SKILLS THROUGH EDUPRENEURSHIP IN VOCATIONAL EDUCATION - Arianto Arianto; Hasan Maksum; Waskito Waskito (STKIP Pesisir Selatan, 2026)
This meta-analysis synthesizes the mixed results of previous empirical studies to determine the magnitude and consistency of the edupreneurship impact on developmental life skills in vocational education. This study adopted a quantitative meta-analytical approach to review 20 national and international journal publications from 2013-2022. The results show that the overall impact of edupreneurship on the development of life skills is large and the average effect size is 0.27, which shows a considerable educational input. Of the life skills, social skills had the highest effect (ES = 0.34), followed by self-knowledge skills (ES = 0.31) and vocational skills (ES = 0.25). The results show how important edupreneurship is in the development of soft skills and work competencies. The findings give theoretical support to experiential learning and human capital perspectives suggesting that entrepreneurship oriented learning environments nurture adaptive, interpersonal and vocational skills needed for work preparation. In practice, the study highlights the importance of integrating edupreneurship through project-based learning, teaching factory models and industry-linked training as a way of providing evidence-based guidance for vocational curriculum development. Thus, there is a need to promote edupreneurship as a basic pedagogical strategy for employability, resilience and life skills in line with the demands of the labour market.